Kegiatan Literasi Perpustakaan sebagai Sarana Pengembangan Minat Baca Anak Usia Dini di TK Masyithoh 25 Sokaraja - Kurniawan, Heru; Prasetyani, Ikom (THUFULA, 2019)
TK Masyithoh 25 Sokaraja library has an important role in developing the reading interest of their students. The activity which is developed is library literacy. Through this library literacy TK Masyithoh 25 Sokaraja is able to develop children's interest in reading. The library literacy activities which developed are the activities of borrowing and returning books, story telling activities for children, and literacy activities of reading aloud. The three activities in turn programmed are followed by students of TK Masyithoh 25 Sokaraja. Through these three activities, students of TK Masyithoh 25 Sokaraja can increase their reading interest which is characterized by: the child's needs for reading books, actions to looking for reading sources ; pleasure in reading; interest in reading; the desire to always read; and follow-up (following up on what they read).